The Role of Activity-Based Teaching on Academic Achievement and Motivation of Secondary School Students in Najran District - Abdulsalam Dale Amer Saif (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
This study aimed to explore the effect of activity-based teaching on academic achievement and motivation of secondary school students in Najran region. An experimental research design was used to collect data from a study sample that consisted of 43 high school students who were randomly selected. The study tools were an achievement test and a motivation scale. These instruments were implemented during the first semester of the academic year 1443/1444. The results of this study showed that the achievement of the students of the experimental group was higher than that of the students of the control group. The results also showed that the majority of students found activity-based teaching more interesting than lecture-based teaching. The study concluded with some recommendations in order to enhance the role of activities in teaching secondary sciences.